On I-Convergence Difference Sequence Spaces Defined by Orlicz Function in 2−Normed Space - Ghimire, Jhavi Lal; Adhikari, Gobinda; Pahari, Narayan Prasad (Journal of Nepal Mathematical Society, 2024)
The difference sequence spaces of type I-convergent, I-null, bounded I-convergent, and bounded I-null in 2−normed space are introduced and studied using the Orlicz function. Investigations into the pertinent characteristics of these spaces led us to the establishment of some inclusion relations.